2016
DOI: 10.1002/cphc.201601037
|View full text |Cite
|
Sign up to set email alerts
|

Wire‐Active Microrheology to Differentiate Viscoelastic Liquids from Soft Solids

Abstract: Viscoelastic liquids are characterized by a finite static viscosity and a zero yield stress, whereas soft solids have an infinite viscosity and a non-zero yield stress. The rheological nature of viscoelastic materials has long been a challenge, and it is still a matter of debate. Here, we provide for the first time the constitutive equations of linear viscoelasticity for magnetic wires in yield stress materials, together with experimental measurements using Magnetic Rotational Spectroscopy (MRS). With MRS, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(74 citation statements)
references
References 62 publications
1
73
0
Order By: Relevance
“…57,58 Note that in the H ( / G )-representation, the continuous line in the figure is obtained with no adjustable parameter. 45,57 In conclusion to this part, it is found that Curosurf® loaded with silica behaves as a Newtonian fluid at all concentrations studied and that the dispersions are characterized by a single rheological parameter, the static shear viscosity . A similar type of behavior can be observed for Curosurf® mixed with alumina at concentrations lower than 31 = 0.1 g L -1 .…”
Section: Ii2 -Nanoparticle Loaded Surfactant Showing a Viscous Fluidmentioning
confidence: 78%
See 1 more Smart Citation
“…57,58 Note that in the H ( / G )-representation, the continuous line in the figure is obtained with no adjustable parameter. 45,57 In conclusion to this part, it is found that Curosurf® loaded with silica behaves as a Newtonian fluid at all concentrations studied and that the dispersions are characterized by a single rheological parameter, the static shear viscosity . A similar type of behavior can be observed for Curosurf® mixed with alumina at concentrations lower than 31 = 0.1 g L -1 .…”
Section: Ii2 -Nanoparticle Loaded Surfactant Showing a Viscous Fluidmentioning
confidence: 78%
“…b, c) H,abc ( * ) for Curosurf® dispersions loaded with alumina particles at 31 = 0.19 and 0.49 g L -1 respectively, * being the reduced wire length defined in the text. The thick red line indicates the 1/ * , -behavior expected from the soft solid model 45. The orange areas denote the range over which the 1/ * , -prefactor varies in these experiments.…”
mentioning
confidence: 92%
“…The magnetic wire microrheology technique has been described in previous accounts [41][42][43]. For reviews on microrheology techniques and data analysis, especially those using anisotropic probes, we refer to Refs [30,31,33,44].…”
Section: Ii8 -Active Microrheologymentioning
confidence: 99%
“…The images show that after a counter-clockwise rotation in the first 3 panels (between 20.5 and 23.0 s after the field inception), the wire comes back rapidly by 40 degrees in a clockwise motion, indicating that the wire does not follow the field in this time interval. The angular frequency at which the transition occurs reads [41,43] :…”
Section: F) the Microscopy Images On The Right-hand Side Show That Afmentioning
confidence: 99%
“…The optical cell equipped with the environment control circuit is fit under the Olympus BX51 upright microscope. We illustrate robustness of this stage by studying viscous properties of liquids with a high-speed rheological technique based on Magnetic Rotational Spectroscopy [4,36,54,55], using magnetic nano-and microrods as the probes.…”
Section: Introductionmentioning
confidence: 99%